Economic impact of climate change on palm oil and paddy production in Malaysia - Zainal, Zahid (2013)
Climate change issues are debated and have heated up to the global stage. Malaysia like other developing countries faces critical issues on global warming which change local climate and threatens agriculture activities. Higher temperatures and erratic rainfall are the most widely climate change indicators known to affect growth of crops. According to IPCC, global temperatures will increase by 1.5oC to 5.8oC by 2100 and challenge sustainability of agricultural sector in future. The purpose of this study was to investigate economic impact of climate change to oil palm and paddy production in Malaysia. It employed a modified Ricardian model to assess impact of climate change on crop productivity. The impact changes in temperature and rainfall for 31 years period (1980 to 2010) on palm oil and paddy production was successfully determined through time-series regression analysis based on annual crops production. Besides, the regression output result was interpreted in agronomic perspective. The PRECIS (Providing Regional Climates for Impacts Studies) Regional Climate Modeling System was applied to estimate potential impact on palm oil and paddy net revenue due to long-term changes in climate. The result shows that temperature and rainfall had significant negative impact to palm oil and paddy production. The total marginal increase of temperature and rainfall resulted in a loss (RM/ha) of about RM31.37, RM47.18 and RM35.92 for Peninsular, Sabah and Sarawak respectively. Meanwhile, the loss in paddy production in Malaysia as a whole is approximately amount to RM312.20. By projection using regional climate modeling system (PRECIS) the palm oil is predicted to lose an average amount of RM444.12, RM294.20, and RM105.62for Peninsular, Sabah and Sarawak respectively in year 2059. Moreover, paddy will record a loss to RM4583.10 in the same year. Therefore, it is recommended that adaptation and mitigation strategies are needed to minimize adverse effects of climate change on oil palm and paddy production.